Self-reported knowledge, attitudes, and practice of final-year dental students in relation to child abuse: A multi-centre study - (:unkn) unknown (WILEY, 2021)
Background The number of child abuse cases is increasing worldwide; therefore, it is important to educate individuals having contact with children about it. This includes dentists who play a pivotal role in detecting and reporting child abuse. Aim To identify and compare the final- year dental student's knowledge, attitudes, and practice in relation to child abuse. Design A 38- item and four- part online questionnaire was distributed to students of 11 dental schools in 10 countries. SPSS and GraphPad Prism were used for data analysis. The levels of statistical significance were determined using a chi- square test. P <= .05 was considered to be statistically significant. Results A total of 660 students completed the survey. Fifty- six percent of the students received formal training on child abuse, and 86% wanted additional training. The knowledge of child abuse was significantly higher in Australia, the United States, and Jordan compared with other countries. Internet (60.3%) was commonly used as an information source for child abuse. Conclusions The study showed that dental students lack knowledge and experience in recognizing and reporting child abuse. Most respondents indicated a desire for additional training; therefore, dental schools should review what they are currently teaching and make changes as appropriate.
Keywords: attitudes; child abuse; dental students; education; knowledge; DENTISTS; MALTREATMENT; NEGLECT; EXPERIENCES